Evolutionary histories impart structure into marine fish heterospecific co‐occurrence networks. Issue 9 (21st May 2019) - Ford, Benjamin M.; Roberts, J. Dale
Abstract: Aim: Understanding the role of interspecific interactions in maintaining diversity, ecosystem function and evolutionary processes is a major challenge in ecology. Historically, antagonistic heterospecific interactions were the focus of many studies, but the importance of facilitative interactions has become increasingly apparent over recent decades. Ecological networks can provide insights into potential interactions among co‐occurring heterospecifics. We compared the structures of temperate and tropical marine fish co‐occurrence networks to estimate their resilience and/or robustness to perturbations. Location: Western Australia. Time period: Present. Major taxa studied: Marine fishes. Methods: We compared the structure of temperate and tropical marine fish communities through interspecific co‐occurrences using joint species distribution modelling. Network analyses identified modules of co‐occurring species and those which play a strong role in the organization of communities. Results: In all study locations, most interspecific co‐occurrences did not differ significantly from random, with positive co‐occurrences being more prevalent than negative non‐random co‐occurrences. The modularity of networks created from interspecific co‐occurrences tended to decrease poleward, with the opposite for species centrality. An increase in functional diversity among co‐occurring species with latitude was detected. Species centrality was greatest among the temperate endemic species, with a positive association between species centrality and intrinsic vulnerability scores. Main conclusions: The differences in community structure between tropical and temperate Western Australian marine fish communities might be attributable, in part, to differing evolutionary histories. The temperate endemic species have co‐evolved in a relatively homogeneous abiotic and biotic environment, whereas the Indo‐Pacific ichthyofauna have evolved in a diverse range of environments. The temperate communities are characterized by: (a) low functional redundancy among co‐occurring species, with endemic species playing keystone roles in community structure; (b) attributes associated with increased vulnerability to perturbations; with (c) many of the species identified as potential keystone species having high intrinsic vulnerability scores and being targeted by fishers.